Fecal Indicator and Pathogenic Bacteria and Their Antibiotic Resistance in Alluvial Groundwater of an Irrigated Agricultural Region with Dairies. Issue 5 (1st September 2015) - Li, Xunde; Atwill, Edward R.; Antaki, Elizabeth; Applegate, Olin; Bergamaschi, Brian; Bond, Ronald F.; Chase, Jennifer; Ransom, Katherine M.; Samuels, William; Watanabe, Naoko; Harter, Thomas
Abstract : Surveys of microbiological groundwater quality were conducted in a region with intensive animal agriculture in California, USA. The survey included monitoring and domestic wells in eight concentrated animal feeding operations (CAFOs) and 200 small (domestic and community supply district) supply wells across the region. Campylobacter was not detected in groundwater, whereas Escherichia coli O157:H7 and Salmonella were each detected in 2 of 190 CAFO monitoring well samples. Nonpathogenic generic E. coli and Enterococcus spp. were detected in 24.2% (46/190) and 97.4% (185/190) groundwater samples from CAFO monitoring wells and in 4.2% (1/24) and 87.5% (21/24) of CAFO domestic wells, respectively. Concentrations of both generic E. coli and Enterococcus spp. were significantly associated with well depth, season, and the type of adjacent land use in the CAFO. No pathogenic bacteria were detected in groundwater from 200 small supply wells in the extended survey. However, 4.5 to 10.3% groundwater samples were positive for generic E. coli and Enterococcus . Concentrations of generic E. coli were not significantly associated with any factors, but concentrations of Enterococcus were significantly associated with proximity to CAFOs, seasons, and concentrations of potassium in water. Among a subset of E. coli and Enterococcus isolates from both surveys, the majority of E. coli (63.6%) and Enterococcus (86.1%) isolates exhibited resistance to multiple (≥3) antibiotics. Findings confirm significant microbial and antibiotic resistance loading to CAFO groundwater. Results also demonstrate significant attenuative capacity of the unconfined alluvial aquifer system with respect to microbial transport. Core Ideas: Systemic surveys of groundwater microbiological quality are performed at site and regional scales. Confined animal systems are chronic sources of pathogens and high enteric microbial loads. Pathogen loading to groundwater is effectively mitigated by alluvial aquifer system. Some microbial indicators are too ubiquitous to be useful as indicators. Antibiotic resistance from CAFOs and human sources affects the alluvial aquifer system.